Engineering Escherichia coli-Derived Nanoparticles for Vaccine Development - Shubing Tang; Chen Zhao; Xianchao Zhu (Vaccines)
The development of effective vaccines necessitates a delicate balance between maximizing immunogenicity and minimizing safety concerns. Subunit vaccines, while generally considered safe, often fail to elicit robust and durable immune responses. Nanotechnology presents a promising approach to address this dilemma, enabling subunit antigens to mimic critical aspects of native pathogens, such as nanoscale dimensions, geometry, and highly repetitive antigen display. Various expression systems, including Escherichia coli (E. coli), yeast, baculovirus/insect cells, and Chinese hamster ovary (CHO) cells, have been explored for the production of nanoparticle vaccines. Among these, E. coli stands out due to its cost-effectiveness, scalability, rapid production cycle, and high yields. However, the E. coli manufacturing platform faces challenges related to its unfavorable redox environment for disulfide bond formation, lack of post-translational modifications, and difficulties in achieving proper protein folding. This review focuses on molecular and protein engineering strategies to enhance protein solubility in E. coli and facilitate the in vitro reassembly of virus-like particles (VLPs). We also discuss approaches for antigen display on nanocarrier surfaces and methods to stabilize these carriers. These bioengineering approaches, in combination with advanced nanocarrier design, hold significant potential for developing highly effective and affordable E. coli-derived nanovaccines, paving the way for improved protection against a wide range of infectious diseases.